2016
DOI: 10.1097/md.0000000000003401
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Transthoracic Echocardiography in Patients With Anomalous Origin of the Left Coronary Artery From the Pulmonary Artery

Abstract: Anomalous origin of the left coronary artery from the pulmonary artery (ALCAPA) is a rare congenital coronary abnormality associated with early infant mortality and sudden death in adults. Transthoracic echocardiography (TTE) plays an important role in early detection and diagnosis of ALCAPA as a noninvasive modality. However, its diagnostic value is not well studied. The purpose of this study is to determine the performance of TTE in the diagnostic assessment of ALCAPA as compared with coronary CT and invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Specifically, TOE can be extremely useful in revealing other potential causes of ischaemic stroke such as spontaneous echo contrast, reduced left atrial appendage velocities, Lambl’s excrescences, intra-atrial septal abnormalities, aortic atheroma, endocarditis (bacterial and non-bacterial), intracardiac tumours and valvular pathologies such as mitral stenosis, atrial myxoma and papillary fibroelastoma 5. Although studies have suggested TTE has a high diagnostic accuracy in ALCAPA,6 7 our case highlights that it cannot be fully relied upon.…”
Section: Discussionmentioning
confidence: 85%
“…Specifically, TOE can be extremely useful in revealing other potential causes of ischaemic stroke such as spontaneous echo contrast, reduced left atrial appendage velocities, Lambl’s excrescences, intra-atrial septal abnormalities, aortic atheroma, endocarditis (bacterial and non-bacterial), intracardiac tumours and valvular pathologies such as mitral stenosis, atrial myxoma and papillary fibroelastoma 5. Although studies have suggested TTE has a high diagnostic accuracy in ALCAPA,6 7 our case highlights that it cannot be fully relied upon.…”
Section: Discussionmentioning
confidence: 85%
“…Most recent literature supports the accuracy of echocardiography, but usually, the diagnosis is confirmed by angiography and/or computed tomography (CT) and magnetic resonance imaging (MRI). [14,15,[18][19][20][21][22] Of note, a poor acoustic image window may be a limitation for echocardiographic evaluation. Invasive coronary angiography remains the gold standard for ALCAPA diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…En estos casos puede utilizarse el Doppler color para obtener informacion del flujo hemodinamico de la misma (Vídeo 4 y Figura 1). Evidenciandose flujo retrogrado en los vasos anomalos originados del tronco pulmonar, ocurriendo principalmente durante la fase diastolica del ciclo cardiaco (1) .…”
Section: Anomalous Origin Of the Left Coronary Artery From The Pulmon...unclassified